The global, regional, and national burden of pediatric stone disease: 1990–2021 and projections for the next two decades - Chen, Sheng; Ma, Xiaohan; Guo, Lin; Wang, Shuaikang; Wu, Junchao; Wu, Lingling; Zhang, Ting; Gao, Hongjun (Frontiers in Pediatrics, 2025)
BackgroundPediatric stone disease, once considered rare, has gained significant attention over the past decade owing to its rapidly increasing incidence. Despite this surge, a comprehensive evaluation of this burden is lacking.ObjectivesThis study aimed to estimate the burden of pediatric stone disease, stratified by age and sex, at the global, regional, and national levels from 1990 to 2021.MethodsData on the global incidence, deaths, and disability-adjusted life years (DALYs) related to pediatric stone disease from 1990 to 2021 were collected. The estimated annual percentage change (EAPC) quantified the disease trends over this period. Additionally, the relationship between disease burden and factors such as age and sociodemographic index (SDI) levels was analyzed. A Bayesian Age-Period-Cohort (BAPC) model was employed to project the future burden from 2022 to 2041.ResultsIn 2021, there were 3,289,663 cases of pediatric stone disease worldwide (95% UI: 1,724,296 to 5,384,797), resulting in 66 deaths (95% UI: 43 to 94) and 14,230 disabilities (95% UI: 9,264 to 21,569). Regionally, South Asia reported the highest incidence, mortality, and DALYs based on the Global Burden of Disease (GBD) classifications. Age-standardized morbidity (ASIR) and age-standardized mortality (ASDR) are highest in Eastern Europe, while age-standardized mortality (ASMR) is 0 in all regions of the world. At the country level, India recorded the highest incidence, mortality, and DALYs for pediatric stone disease in 2021. Armenia had the highest ASIR, while 28 countries, including Afghanistan, Armenia, and Brazil, reported the highest ASMR. Armenia and Kazakhstan recorded the highest ASDR. The disease burden was most pronounced among children aged 15–19 years, with boys being more affected than girls. These findings have significant global implications. Projections indicate that by 2041, the burden of pediatric stone disease will decline, although boys will continue to be more affected than girls.ConclusionFrom 1990 to 2021, the global burden of pediatric stone disease, adjusted for age, has decreased. However, regional variations persist, with some areas experiencing an increase in burden. This underscores the importance of ongoing monitoring to effectively reduce the overall impact of pediatric stone diseases.